Use of Advanced Piston Ring Coatings on Agricultural Engines - Xiaochao He; Bang Liu; Eduardo Tomanik; Grzegorz Koszalka; Anna Orlova (Lubricants)
The use of combustion engines on agricultural vehicles will persist much longer than on-road vehicles. Introducing new technologies in agricultural engines is crucial to mitigating emissions while accounting for customer cost-sensitivity, harsh operation conditions, and typically sub-optimal maintenance. This work describes the use of CrN and tetrahedral amorphous carbon (ta-C) DLC-coated rings in small agricultural diesel engines. Compared with the gas nitride rings, the CrN and the ta-C DLC coatings exhibited, respectively, 74% and 86% lower wear in rig tests. The DLC also presented a very low coefficient of friction and high resistance to scuffing. A similar wear trend was observed on durability engine tests, where the CrN top ring showed an 80% lower wear rate than the GNS used in a similar engine. Wear on the DLC oil ring was below the measurement capability. Liner radial wear was measured on the piston ring reversal points in four angular positions, and except for one position, was lower than 3 µm. At the end of the test, engine performance and emissions are nearly identical to those at the test’s start, demonstrating that the use of advanced tribological solutions can significantly contribute to emissions mitigation in agricultural engines.